Efektivitas Green Advertising terhadap Purchase Intention pada Green Cosmetic Product - Cindyviera Zuriel Questania; Khoyimatus Sa’adha; Shuhaima; Reval Furqon Nugraha; Yaumul Rahmi (Flourishing Journal, 2024)
Today, the need for skin care and make-up is a concern for women. Therefore, marketers in the cosmetics industry are using different ways to attract buyers, one of which is the technique of green advertising. This study was conducted to determine whether green advertising influences purchase intention for Love Beauty and Planet products. This research is an experimental study with a two-group design. In this study, the experimental group was exposed to green advertising while the control group was not exposed to green advertising. The results of the assumption test showed that the data were not normally distributed, so the researchers used the non-parametric Mann-Whitney U test to test the hypothesis. The results of the hypothesis test show that green advertising affects purchase intention for Love Beauty and Planet products, which is consistent with previous studies. This study proves that green advertising effectively increases consumers' purchase intention for Love Beauty and Planet products. It means that when consumers are exposed to advertisements that highlight the green theme of a product (such as Love Beauty and Planet), they tend to be more interested in buying the product. AbstrakSaat ini, kebutuhan akan skincare dan make up menjadi perhatian para wanita. Sehingga para pelaku industri kosmetik melakukan berbagai cara untuk menarik minat pembelinya, salah satunya adalah teknik pengiklanan dengan green advertising. Penelitian ini dilakukan untuk melihat apakah green advertising memiliki pengaruh pada purchase intention untuk produk Love Beauty and Planet. Penelitian ini menggunakan pendekatan eksperimen desain dua kelompok. Pada penelitian ini kelompok eksperimen diberikan paparan berupa green advertising sedangkan pada kelompok kontrol tidak diberikan green advertising. Hasil uji asumsi menunjukkan bahwa data tidak berdistribusi normal, sehingga peneliti menggunakan uji non parametrik Mann-Whitney U untuk menguji hipotesis. Hasil uji hipotesis menunjukkan bahwa green advertising berpengaruh terhadap purchase intention pada produk kosmetik Love Beauty and Planet. Penelitian ini membuktikan bahwa green advertising efektif dalam meningkatkan purchase intention terhadap produk Love Beauty and Planet. Hal ini berarti ketika konsumen dihadapkan pada iklan yang mengangkat tema green (ramah lingkungan) dari suatu produk (seperti Love Beauty and Planet), mereka cenderung lebih tertarik untuk membeli produk tersebut.